If the roots of equation (b -c) x² + (c-a) X
+ (a - b) = 0 are equal prove that 2b = a + c.
Answers
Answered by
7
Answer:
hope it helps you
please mark brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d20/abd28c925dfb00c17471038317506f64.jpg)
Answered by
14
If the roots of eqn (b-c) x² + (c - a) x + ( a- b) = 0 are equal , prove that 2 b = a + c .
In any quadratic eqn of the form
ax² + bx + c = 0
Discriminant represented by 'D' is given by
● If D < 0 then the quadratic eqn will have no real roots.
● If D = 0 then the quadratic eqn will have two real and equal roots.
● If D > 0 then quadratic eqn will have two distinct real roots.
_______________________________
Know the algebraic identity
Given Quadratic eqn is
As given That roots of this eqn are equal
Therefore,
Discriminant = 0
Solving and
Rearranging the terms
Using algebraic identity
Proved.
Similar questions